The influence of tax service quality and tax socialization on individual taxpayer compliance in the regional tax office of the Riau Islands - Sutanto, Meithasya Putri (Educoretax, 2024)
This research investigates how taxpayer compliance at the Riau Islands Regional Tax Office is affected by two factors: the quality of tax services and tax socialization efforts. The researchers surveyed 116 individual taxpayers and analyzed their responses using regression analysis. The findings revealed that both factors positively influenced compliance levels. Specifically, each unit improvement in tax service quality led to a 0.227 unit increase in compliance, while each unit increase in tax socialization resulted in a 0.479 unit rise in compliance. Together, these two factors account for 34.9% of the variations in taxpayer compliance behavior. Based on these results, the study recommends enhancing both service quality and socialization activities to boost tax compliance in the region.